Celiac Disease and the Susceptibility of COVID-19 and the Risk of Severe COVID-19: A Mendelian Randomization Study. Issue 5 (28th May 2022) - Li, Jiuling; Tian, Aowen; Yang, Dandan; Zhang, Miaoran; Chen, Lanlan; Wen, Jianping; Chen, Peng
Abstract : INTRODUCTION: Previous observational studies have found that the susceptibility of coronavirus disease 2019 (COVID-19) and the risk of severe COVID-19 are not increased in patients with celiac disease (CeD). However, the findings of observational studies are prone to bias due to reverse causation and confounding factors, especially in the case of a newly emerged disease. In this study, we aimed to further clarify the underlying relationship by both observational and Mendelian randomization (MR) analysis. METHODS: This observational study was conducted in the UK Biobank cohort. Univariate and multivariate logistic regression analyses were performed to identify the risk factors of COVID-19 susceptibility and severe COVID-19. To understand the causality between CeD and COVID-19 susceptibility and severe COVID-19, we performed a 2-sample MR analysis. RESULTS: Our observational study showed that patients with CeD had a lower susceptibility of COVID-19 (odds ratio [OR] = 0.699, P = 0.006) while CeD was not significantly associated with severe COVID-19 ( P > 0.05). The findings from our MR study further demonstrated that both the susceptibility to COVID-19 (OR = 0.963, P = 0.006) and severe COVID-19 (OR = 0.919, P = 0.049) were lower in patients with CeD, although the former seemed to be specific to the UK Biobank cohort. DISCUSSION: Our results suggested that it may be unnecessary to take extra COVID-19 precaution in patients with CeD.